Structural change in the world economy : main features and trends - Memedovic, Olga (UNIDO ViennaAT, 2010)
Gives a short summary of the relevant theoretical and empirical literature on structural change. Describes the main structural changes that have transformed the world economy in the last four decades. Focuses on the transformation of the manufacturing sector in the last 40 years. Summarises the main trends observed.